Factors affecting the decision of selection the green growth: The case of business firms and its accountancy policy - Pham Thi Thuy Hang (Decision Science Letters, 2024)
Economic development is required to be associated with sustainable environmental protection and is considered as an urgent need in the current period. Research on the factors that determine the use of green production activities is carried out in Vietnam through a survey of 202 businesses, through Cronbach's alpha reliability analysis method, exploring EFA factors and regression analysis, research results show that the benefits of green growth, the effectiveness of communication and the quality of human resources have a positive impact on promoting green growth, while there is no influence of state policies on green growth.